Comparisons of Core Temperature Between a Telemetric Pill and Heart Rate Estimated Core Temperature in Firefighters - Stephen J. Pearson; Brian Highlands; Rebecca Jones; Martyn J. Matthews (Elsevier, 2022)
Background: Firefighters may experience high environmental temperatures or carry out intensive physical tasks, or both, which leads to increased core body temperature and risk of fatalities. Hence there is a need to remotely and non-invasively monitor core body temperature. Methods: Estimated (heart rate algorithm) and actual core body temperature (ingested telemetric pill) measures were collected simultaneously for comparison during training exercises on 44 firefighter volunteers. Results: Prediction of core body temperature varied, with no specific identifiable pattern between the algorithm values and directly measured body core temperatures. Group agreement of Lin's Concordance of 0.74 (95% Upper 0.75, lower CI 0.73), was deemed poor. Conclusion: From individual agreement data Lin's Concordance was variable (Min 0.11, CI 0.13-0.01; Max 0.83, CI 0.86-0.80), indicating that the heart rate algorithm approach was not suitable for core body temperature monitoring in this population group, especially at the higher more critical core body temperatures seen.